Pengaruh Budaya Organisasi Dan Empowerment Terhadap Komitmen Organisasi - Faiqotul Isma Dwi Utami; Dhelittya Finaliyani Putri (FAI- Undar, 2022)
The purpose of this research is to analysis effect of organizational culture, empowerment and organizational commitment among teachers at Islamic Junior High School of Nahjatus Sholihin Plawangan Kragan Rembang. The population and sample in this research is all the teachers at Islamic Junior High School of Al Hidayah Desa Wedoro Kec. Glagah Lamongan which is 31 teachers and employees, because the population is less than 100 in its account, then the sample is taken from that population. Design of this research is quantitative research because testing relationship between three variable there is Organizational culture, Empowerment and Organizational commitment. Collecting data methods using questionnaire which is given to all the teachers at Islamic Junior High School of Al Hidayah Desa Wedoro Kec. Glagah Lamongan as the respondents than it is analyzed using pearson effect of and proceed with 17th version of SPSS software. Based on the analysis results indicate a trend most of the respondents consider the principal's organizational culture at Islamic Junior High School of Al Hidayah Desa Wedoro Kec. Glagah Lamongan is good enough. Empowerment of the principal teacher at Islamic Junior High School of Al Hidayah Desa Wedoro Kec. Glagah Lamongan already good but needs to be increased again. There is a significant positive effect (partial and simoultansly) organizational culture and empowerment on organizational commitment among teachers at Islamic Junior High School of Al Hidayah Desa Wedoro Kec. Glagah Lamongan. Based on the results of this study, the authors give advice to all stakeholders to further empower teachers and employees in teaching and learning process at Islamic Junior High School of Al Hidayah as an effort to increase organizational commitment in school. For madrasah is expected to apply the values reflected in Islamic culture as an effort to increase employee work commitment.